Wege aus der Wachstumsschwäche - Veronika Grimm; Thilo Kroeger; Christian Ochsner (Wirtschaftsdienst, 2024)
Deutschland erlebt derzeit einen erheblichen Rückgang seines Produktionspotenzials. Wesentliche Ursache ist die demografische Alterung und insbesondere der Eintritt der geburtenstarken Jahrgänge (Baby-Boomer) in den Ruhestand. Das verfügbare Arbeitsvolumen wird darüber hinaus durch niedrige Erwerbsquoten bei älteren Erwerbspersonen sowie ein Absinken der durchschnittlichen Arbeitsstunden verstärkt. Um die Wachstumsschwäche zu überwinden, muss die Fähigkeit der Volkswirtschaft gestärkt werden, das Produktionspotenzial durch technologischen Fortschritt und die effiziente Nutzung von Ressourcen zu steigern. Der vorliegende Beitrag analysiert die Entwicklung des Wachstumspotenzials, quantifiziert die möglichen Beiträge zur Überwindung der Wachstumsschwäche und skizziert abschließend wirtschaftspolitische Handlungsoptionen. – – Germany is experiencing a significant decline in potential output. The main reason is demographic aging and, in particular, the retirement of the baby boomers. The available labour volume is also being exacerbated by low employment rates among older workers and a decline in average working hours. In order to overcome weak growth, it is key to strengthen the economy's potential output through technological progress and the efficient allocation of resources. This article analyses the development of potential output growth, quantifies possible contributions to overcoming weak growth and concludes by outlining economic policy options. We discuss two areas that are important for strengthening potential growth: mitigating the consequences of demographic aging and increasing investment and innovation. Mitigating the aging effects requires measures to increase labour market participation and the substitution of labour with capital goods where possible. The latter helps to ensure that more workers become available in areas where substitution through automation is more difficult. Increasing investment and innovation is crucial in order to increase productivity, modernise and expand the capital stock and open up new growth areas.
Keywords: O40; E23; J21; 330; Konjunktur; Produktionspotenzial; Deutschland; Konjunktur; Produktionspotenzial; Deutschland